ANALISA DAN PERANCANGAN SISTEM INFORMASI PENGADAAN BARANG - Enty Nur Hayati; Antono Adhi (Jurnal Ilmiah Dinamika Teknik, 2010)
Information era and globalization cause natural business environment very fast change with tight emulation story level. Therefore companies claimed to operational activity effectively and efficient to maintaining its. Information system also needed in levying of goods for the fluency of process purchasing of goods of supplier and also to buyer. Goods purchasing procedure entangle some part in company for the purpose of execution of purchasing of goods can observe better. One of the ‘cause the happening of chaos in goods purchasing procedure is weakening of internal control at procedure and system arranging an transaction. To overcome the problem, hence each; every company require to compile a[n procedure and system able to create good internal control in arranging execution of transaction of corporation. Purpose which is needed in system development of Levying of Goods is arrangement of material requisition, that is function arranging goods which must be ordered, by request of other units, with supplier which have been determined, ordering of goods, that is function to order goods to supplier and arrangement of supplier, that is function to arrange new supplier and arrange which supplier to provide material.   Keywords: Product purchasing, supplier, system design analysis